Effect of Dietary Supplementation of Oregano (Oreganum vulgare) Essential Oil on Nutrient Utilization and Haemato-biochemical Profile of Growing Japanese Quail - Thawker, Piyush Dhanraj; Kumari, Kiran; Archana; Prusty, Sonali; Pal, Prasanna; Gendley, M. K. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the month of June in 2022 at the Poultry Experimental Unit, Department of Animal Nutrition, College of Veterinary Science and Animal Husbandry, Anjora, Durg, Chhattisgarh, India to evaluate the effect of dietary supplementation of oregano (Origanum vulgare) essential oil on nutrient utilization and haemato-biochemical parameters in broiler quails. Total 240 Japanese quail chicks procured from the college hatchery were randomly assigned to four groups: T0 (control), T1 (75 mg kg-1), T2 (150 mg kg-1), and T3 (225 mg kg-1) on a dry matter basis. Birds received a formulated concentrate mixture during the starter and finisher phases. Oregano oil significantly (p<0.01) improved intake, outgo, and digestibility of dry matter (DM), crude protein (CP), and ether extract (EE). Haemoglobin and total erythrocyte count increased significantly in T3, while packed cell volume and total leucocyte count remained unaffected (p>0.05). Serum AST and ALT levels were significantly lower in T3 (160 and 19.26 IU l-1) compared to T0 (213.33 and 29.93 IU l-1), while total protein and globulin increased with supplementation. Albumin and A:G ratio showed no significant change. Cholesterol was significantly reduced in T3 (182.44 mg dl-1) versus control (211.20 mg dl-1). Oregano essential oil up to 225 mg kg-1 can be safely included in quail diets to enhance nutrient utilization and physiological health.